2019
DOI: 10.1029/2018wr024324
|View full text |Cite
|
Sign up to set email alerts
|

Simulation Model for Collaborative Decision Making on Sediment Source Reduction in an Intensively Managed Watershed

Abstract: We developed a watershed sediment source and delivery model for use in evaluating conservation trade-offs in southern Minnesota, where sediment loading has been identified as a priority and there is substantial public investment in cleaner water. The model was developed in a stakeholder process and links user-specified management options to reductions in sediment loading at the outlet of a 2,880-km 2 intensively farmed watershed. The simulation model was formulated to allocate total sediment load among sources… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…We overcame this barrier by integrating three biophysical models into one agricultural field-to-river integrated model, hereafter referred to as the AgRiver model. The framework integrates two models of near-channel processes: the Nitrate Network Model (NNM) (39) and the Management Option Simulation Model (MOSM) (40), with the Soil and Water Assessment Tool (SWAT), a watershed model that is widely used to assess field management effectiveness (41). Using the AgRiver model and an evolutionary optimization approach, we compared performance of watershed management portfolios based on their ability to simultaneously reduce nitrate loads (N), sediment loads (S), and cost across a broad range in reduction targets.…”
Section: Significancementioning
confidence: 99%
“…We overcame this barrier by integrating three biophysical models into one agricultural field-to-river integrated model, hereafter referred to as the AgRiver model. The framework integrates two models of near-channel processes: the Nitrate Network Model (NNM) (39) and the Management Option Simulation Model (MOSM) (40), with the Soil and Water Assessment Tool (SWAT), a watershed model that is widely used to assess field management effectiveness (41). Using the AgRiver model and an evolutionary optimization approach, we compared performance of watershed management portfolios based on their ability to simultaneously reduce nitrate loads (N), sediment loads (S), and cost across a broad range in reduction targets.…”
Section: Significancementioning
confidence: 99%
“…Many of our research findings have immediate and direct implications on federal and state policies, planning, and restoration strategies. For example, our approach has demonstrated the enormous potential for wetlands to abate nitrogen and sediment transport at watershed scales (Cho et al, ; Hansen et al, ; Mitchell et al, ), with wetland installation shown to be 5 times more effective at reducing nitrate than field‐based approaches (i.e., cover crops) under high to moderate flows (Hansen et al, ). At the same time, stakeholder‐driven modeling of management options to reduce sediment loading enabled consensus agreement among our stakeholder group for hydrology management to be included as an integral part of management portfolios focused on sediment reduction (Cho et al, ).…”
Section: Discussion: Opportunities Enabled By Observatory‐scale Effortsmentioning
confidence: 99%
“…Sediment fingerprinting (described below) provided an independent constraint on sediment partitioning. The integrated sediment budget formed the foundation for investigations into landscape evolution in incising basins (Belmont, ; Gran et al, ); reduced complexity sediment routing and delivery models (Cho et al, ; Cho, ; Czuba et al, ; Gran & Czuba, ; Viparelli et al, ); investigation of the contribution of sediment sources to a watershed‐scale phosphorus budget (Baker, ); and participatory modeling efforts with stakeholders to determine optimal combinations of hydrology, field, and near‐channel management options to cost‐effectively reduce sediment loading in the GBERB (Cho et al, ; Cho, ; Cho et al, ; Lang & Rabotyagov, ).…”
Section: New Interdisciplinary Data Sets For Watershed‐scale Studies mentioning
confidence: 99%
See 2 more Smart Citations